Nurses' perspectives on professional self-concept and its influencing factors: A qualitative study - Chuyuan Miao; Chunqin Liu; Ying Zhou; Xiaofang Zou; Liqin Song; Joanne W.Y. Chung; Wenying Tan; Xiaohua Li; Dong Li (BMC, 2024)
Abstract Background Nurses with a strong professional self-concept tend to exhibit a positive mindset and strong work engagement, delivering high-quality patient care. Although numerous quantitative studies have examined the factors impacting professional self-concept, there remains a limited exploration of these factors from the perspective of nurses themselves. Methods This qualitative descriptive study uses the PERMA theory and Social Cognitive Theory as the theoretical framework. Semi-structured interviews were conducted with 15 nurses from six public hospitals in China. The data were analyzed thematically using a combination of inductive and deductive approaches. Results Nurses' understanding of professional self-concept could be divided into four categories: professional identity, competence, care, and knowledge. Factors influencing nurses' professional self-concept were categorized into eight subthemes in three domains: (1) personal factors, including psychological qualities and attitude towards the nursing profession; (2) occupational-related behavioral factors, including role-oriented behavior and knowledge-oriented behavior; and (3) work environment and external factors, including external evaluation and perceptions of nurses, time allocation, nursing work tasks, work atmosphere, school education, and perceived supports. Conclusions This study found that, although nurses had different personal experiences, their perceptions of professional self-concept were similar. Nurses' professional self-concept is a multidimensional concept and involves various factors, such as personality, work-related characteristics, environment, and family. To thrive in a nursing career, nurses must discern the factors that can enhance or hinder their professional self-concept. By identifying and adjusting these factors, personalized support and positive interventions can be tailored to meet nurses' specific needs, which ultimately nurtures their professional development. Trial registration This study was registered on December 14, 2022, in the Chinese Clinical Trial Registry (ChiCTR2200066699) as part of our ongoing study.